1987
DOI: 10.1002/em.2860090204
|View full text |Cite
|
Sign up to set email alerts
|

Disubstituted amino‐, nitroso‐, and nitrofluorenes: A physicochemical basis for structure‐activity relationships in salmonella typhimurium

Abstract: Twenty-nine derivatives of fluorene were tested for mutagenic potency in four strains of Salmonella typhimurium with and/or without S9 microsomal activation. The effects of a second functional group on the mutagenic activity of an amino-, nitroso-, and nitrofluorene were correlated with its physical and chemical properties. When the functional group is conjugated by resonance, both inductive and resonance effects are determinants of mutagenic potency. Electron-withdrawing groups such as the halogens (F, C1, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 65 publications
4
21
0
Order By: Relevance
“…Analogous studies of other groups of chemicals having a broad range of mutagenic potency in Salmonella have been reported in the following references: nitro-and aminoaromatics, Vance and Levin [1984], Vance et al, [1985Vance et al, [ , 1986Vance et al, [ , 1987; nitroarenes, Maynard et al, [1986]; and nitronaphthofurans, Arnaise et al, [ 19861.…”
Section: Introduction Historicalmentioning
confidence: 99%
“…Analogous studies of other groups of chemicals having a broad range of mutagenic potency in Salmonella have been reported in the following references: nitro-and aminoaromatics, Vance and Levin [1984], Vance et al, [1985Vance et al, [ , 1986Vance et al, [ , 1987; nitroarenes, Maynard et al, [1986]; and nitronaphthofurans, Arnaise et al, [ 19861.…”
Section: Introduction Historicalmentioning
confidence: 99%
“…The mechanism of genotoxicity is thought to involve metabolic reduction of these nitro-PAHs, so that reduction of the nitro group is considered a key metabolic reaction in the activation of 2-nitrofluorene to mutagens (McCoy et al, 1981;Vance et al, 1987) and ultimate carcinogen (Beije and Möller, 1988). In our previous study, it was demonstrated that 2-nitrofluorene was mainly metabolized to 2-aminofluorene and its acylated metabolites in rat and dog (Ueda et al, 2001).…”
mentioning
confidence: 99%
“…Partially purified fractions containing xanthine oxidase activity showed immunoreactivity against anti-rat xanthine oxidase. The authors (Ueda et al 2003) conclude that in rat skin xanthine oxidase is important for the nitroreduction (at least of the substrate used, 2-nitrofluorene), a metabolic step in the activation of nitroarenes to electrophilically reactive mutagens (Vance et al 1987). …”
Section: Xenobiotica-metabolizing Enzymes In the Rat Skinmentioning
confidence: 99%